2012
DOI: 10.1136/jech-2012-201540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a free school breakfast programme on children's attendance, academic achievement and short-term hunger: results from a stepped-wedge, cluster randomised controlled trial

Abstract: BackgroundFree school breakfast programmes (SBPs) exist in a number of high-income countries, but their effects on educational outcomes have rarely been evaluated in randomised controlled trials.MethodsA 1-year stepped-wedge, cluster randomised controlled trial was undertaken in 14 New Zealand schools in low socioeconomic resource areas. Participants were 424 children, mean age 9±2 years, 53% female. The intervention was a free daily SBP. The primary outcome was children's school attendance. Secondary outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 30 publications
0
82
0
2
Order By: Relevance
“…The deterioration of behavior following breakfast in the less well-equipped schools could reflect greater difficulties in accurately observing whether children are on-task or off-task when they do not have their own desk or are in overcrowded classrooms. In developed high income countries where school infrastructure is more standardized and where classrooms are not overcrowded, this possibly spurious effect is less likely to occur (Murphy et al, 2011;Ni Mhurchu et al, 2013). However, negative effects on behavior have also been reported in UK primary and secondary school children within deprived areas following a SBP (Shemilt et al, 2004).…”
Section: Intervention Studiesmentioning
confidence: 91%
See 3 more Smart Citations
“…The deterioration of behavior following breakfast in the less well-equipped schools could reflect greater difficulties in accurately observing whether children are on-task or off-task when they do not have their own desk or are in overcrowded classrooms. In developed high income countries where school infrastructure is more standardized and where classrooms are not overcrowded, this possibly spurious effect is less likely to occur (Murphy et al, 2011;Ni Mhurchu et al, 2013). However, negative effects on behavior have also been reported in UK primary and secondary school children within deprived areas following a SBP (Shemilt et al, 2004).…”
Section: Intervention Studiesmentioning
confidence: 91%
“…Both Ni Mhurchu et al (2013) and Murphy et al (2011) reported no significant effects of a 1 year SBP on hyperactivity, inattention, emotional symptoms, conduct and peer relationship problems, and pro-social behavior in children. However, in both trials, SBP attendance was low and variable, limiting the potential impact on behavior.…”
Section: Rating Scales and Questionnairesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United Kingdom, a programme that subsidized milk for school children was initiated in 1934 and milk was provided free afterwards (Baker et al, 1980). In a stepped wedge cluster randomized trial, Mhurchu et al (2010) studied the effects of a free school breakfast programme on achievement, psychosocial function, nutrition and school attendance among primary school children in New Zealand and they reported that school breakfast programmes initiated had beneficial outcomes on students' attendance, psychosocial functioning and school grades of the students. correspondingly, Kristjansson et al (2007) conducted a review on school feeding designed for improving the physical and psychosocial health of disadvantaged students and reported that there were significant weight gains in kilogramme and height gain in centimeter and bone density.…”
Section: Introductionmentioning
confidence: 99%